GIS-BASED SPATIAL MODEL FOR HABITAT SUITABILITY OF BABIRUSA (BABYROUSA CELEBENSIS), IN GORONTALO PROVINCE - Rosyidy, Muhamad Khairul; Wibowo, Adi (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2020)
Babirusa (Babyrousa celebensis) is an endemic animal from Gorontalo Province whose population is declining day by day due to poaching, land clearing, and selling babirusa meat in traditional markets in Gorontalo Province. Since 1931 this species has begun to be protected in Indonesia, and since 2008, International Union for Conservation of Nature (IUCN) named the babirusa species as a vulnerable category. This study aims to determine the suitability of babirusa habitat areas (Babyrousa celebensis) in Gorontalo Province with a Geographic Information System (GIS) approach and to determine the relationship of physical characteristics for the habitat of the babirusa habitat in Gorontalo Province. The variables are land use, slope, and elevation. The method used is GIS spatial modeling with overlay analysis. From the results of the analysis, it has concluded that a suitable area as a babirusa habitat is only about 33% of the total area of Gorontalo Province and there are types of land use in the wilderness and swamps at an elevation of 0-500 msl with sloping 0-8%. The validation test shows that Coefficient kappa is 0.16 and overall accuracy is 58%. Therefore, further research is needed by adding other variables to delineate the spatial distribution of babirusa